Clinical characteristics of AATD-related COPD patients vary with age at diagnosis: data from the EARCO international registry - Karadoğan, Dilek; Torres-Duran, María; Tanash, Hanan; Rodríguez-García, Carlota; Jensen, Jens-Ulrik Stæhr; Corsico, Angelo Guido; López-Campos, José Luis; Chapman, Kenneth; Clarenbach, Christian; Guimaraes, Catarina; Bartošovská, Eva; Sucena, Maria; et al. (BMC pulmonary medicine, 2025)
BACKGROUND: This study aims to evaluate the clinical characteristics of COPD patients with AATD according to their age at diagnosis. METHODS: Data was obtained from the European Alpha-1 Research Collaboration (EARCO) registry, an international prospective cohort study. AATD patients with COPD registered between February 2020 and October 2024 were analysed. Clinical charateristics were compared between groups, stratified by age of AATD diagnosis as follows; <45, 45-65 and ≥65 years. A multivariable logistic regression model explored factors associated with age at diagnosis. RESULTS: A total of 1,565 AATD-COPD patients were included, with 18.2% receiving an AATD diagnosis at age ≥ 65. In univariate comparisons according to diagnosis age revealed that the prevalence of patients with Pi*ZZ mutation was lower in the ≥ 65 age group (47.1%) compared to the 45-65 (65.5%) and < 45 (78.5%) age groups. In contrast, the prevalence of Pi*SZ and Pi*SS were higher in the ≥ 65 group compared to the younger age groups. The proportion of never-smokers was highest in the ≥ 65 group (39.5%), whereas only 15.3% of patients under 45 were never-smokers. Multivariate analysis showed that; compared to never-smokers, former smoking (OR: 0.08; 95% CI: 0.03-0.23) and current smoking (OR: 0.43; 95% CI: 0.27-0.70) were negatively associated with a diagnosis at age ≥ 65 in all sample. Compared to the Pi*ZZ genotype, among all sample, Pi*SS was associated with more than a 3-fold increased likelihood of diagnosis at age ≥ 65 and when considering only index cases Pi*SZ was associated with diagnosis age of ≥ 65 (OR: 2.01, 95%CI: 1.01-4.04). Among patients with the Pi*ZZ, current smoking was negatively associated (OR:0.24,95%CI: 0.13-0.47) with a diagnosis at age ≥ 65, whereas higher FEV1% and serum AAT levels were positively associated with later diagnosis. CONCLUSION: Patients diagnosed at an older age had lower tobacco exposure and less severe disease. This suggests that subclinical symptoms may contribute to delays in diagnosis, as COPD features can be subtle or under-recognised until later in life. Our findings highlight the importance of considering AATD in all COPD patients, regardless of age, to avoid missed or delayed diagnoses.
Keywords: Diagnosis age; logistické modely; Smoking; Female; Europe; Prevalence; Age Factors; ženské pohlaví; Logistic Models; kouření; Registries; věkové faktory; lidé; Evropa; Pulmonary Disease, Chronic Obstructive; COPD; prevalence; chronická obstrukční plicní nemoc; prospektivní studie; Male; Aged; Prospective Studies; alpha 1-Antitrypsin Deficiency; Elderly; lidé středního věku; registrace; deficit alfa1-antitrypsinu; AATD; senioři; mužské pohlaví; Middle Aged; Humans